Thermokinetics synergistic effects on co-pyrolysis of coal and rice husk blends for bioenergy production. (15th June 2022) - Tauseef, Maham; Ansari, Abeera Ayaz; Khoja, Asif Hussain; Naqvi, Salman Raza; Liaquat, Rabia; Nimmo, William; Daood, Syed Sheraz
Graphical abstract: Highlights: Kinetic study to investigate mechanistic behaviour of rice husk and coal blends. Chemical, one-dimensional diffusional, and phase interfacial reaction models exhibited thermokinetic rate parameters for 200 °C–400 °C and 410 °C–560 °C temperature ranges. Synergistic effects were observed in 80:20 and 60:40 coal-rice husk blends with positive deviation 15–20% bio-oil yield with characterised bio-char. Thermodynamics of selected blends were investigated for further uptake in co-gasification. Application of co-gasification method to produce 14–17% H2 for bioenergy production. Abstract: In-depth thermodynamic and kinetic synergistic effects of the coal and rice husk blends on co-pyrolysis have been investigated for bioenergy production. The thermokinetic rate parameters were determined for chemical, one-dimensional diffusional, and phase interfacial reaction models especially when fitted to the Coats-Redfern method. The fitted models exhibited thermokinetic rate parameters. The thermogravimetric analysis in view of the thermodynamic parameters including enthalpy, Gibbs free energy, and entropy imparted the prominent degradation temperature ranges (Stage A: 200 °C–400 °C, Stage B: 410 °C–560 °C) for co-pyrolysis reactions of blends. The proportional increase of rise husk into coal for Stage A caused an increase in the apparent values of activation energy, enthalpy specifically for one-dimensional diffusional, and phase interfacial reaction models. In case of Stage B, the increasing share of rice husk into coal proved to be beneficial in decreasing values of activation energy and enthalpy. Positive synergies for 80:20 and 60:40 coal-rice husk blends were calculated. In addition to characterisation analysis of all samples; co-pyrolysis and co-gasification experiments were completed in a tubular fixed bed reactor at Stage B and onwards temperatures for synergised blends. The resultant co-pyrolysis biochar samples revealed honeycomb structure useful in adsorption applications. The gas chromatography-mass spectrometry analysis of the bio-oil yields 23% phenols, 11% acids, and methoxy phenols for the 60:40 coal-rice husk blend. The product gas composition of 2% H2, 14% CH4, and 4% CO2 for the 80:20 coal-rice husk blend increased to 3% H2, 12% CH4, and 5% CO2 for the 60:40 blend. The co-gasification process substantially increased the production of H2 up to 14%-17% when compared to co-pyrolysis results. The approach used in this study can be utilized to capitalize on synergy to enhance co-pyrolysis of appropriate blends and their products can be used in further future applications upon upgradation.